Consumers perceptions about the welfare of farm animals in Colombia - García Castro, Fredy E.; Medrano-Galarza, Catalina; Cubides-Cárdenas, Jaime A.; Zúñiga López, Aldemar; Ahumada-Beltrán, Diego G. (Agronomía Mesoamericana, 2022)
Introduction. Research focused on listening and understanding public attitudes towards farm animal welfare is proliferating globally. Objective. To determine how consumers in Colombia perceive the welfare of farm animals and socio-demographic factors associated with such perceptions. Materials and methods. A descriptive and analytical epidemiological study was done through the implementation of a cross-sectional national online survey, conducted from September to October-2021, to obtain information on the knowledge and attitudes of consumers (≥18 years) in Colombia regarding farm animal welfare, as well as socio-demographic characteristics (sex, age, education, occupation, location, growing-up environment, level of contact with livestock farms, and diet). Logistic and multinomial logistic regression models were used to evaluate associations of demographic factors with the level of importance given to animal welfare (AW), perceptions about needs, behavior, and sentience in farm animals, and perceptions about the state and promotion of AW in Colombia. Results. Responses from 798 participants were included in the analysis, 85.57 % saw AW as a concept that refers to how to treat animals and improve their quality of life. The level of importance given to AW was 9.78±0.85 (scale from 0 to 10) and was associated with words such as health, food, caring, respect, and comfort. Sex, age, education, level of contact with a farm, and growing-up in rural areas significantly influenced the opinions regarding the concept of AW and the promotion of farm animal welfare in Colombia. Conclusion. The participants showed concern about farm animal welfare. The differences found associated with the different socio-demographic factors can be used as a basis for formulating education and empowerment strategies that help modulate changes in the way animals are seen, and what welfare means and what it implies.